2015
DOI: 10.1161/circinterventions.114.002049
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Arterial Access Site on Outcomes After Primary Percutaneous Coronary Intervention

Abstract: Background-In European Ambulance Acute Coronary Syndrome Angiography (EUROMAX), bivalirudin improved 30-day clinical outcomes with reduced major bleeding compared with heparins plus optional glycoprotein IIb/IIIa inhibitors. We assessed whether choice of access site (radial or femoral) had an impact on 30-day outcomes and whether it interacted with the benefit of bivalirudin. Methods and Results-In EUROMAX, choice of arterial access was left to operator discretion. Overall, 47% of patients underwent radial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…The utilization of radial (RA) over femoral arterial access (FA) for acute coronary intervention in ST‐elevation myocardial infarction (STEMI) is supported by a reduction in mortality, ischemic, and bleeding endpoints 1, 2, 3, 4, 5, 6, 7, 8. This has led various interventional societies to encourage its utilization over femoral access 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of radial (RA) over femoral arterial access (FA) for acute coronary intervention in ST‐elevation myocardial infarction (STEMI) is supported by a reduction in mortality, ischemic, and bleeding endpoints 1, 2, 3, 4, 5, 6, 7, 8. This has led various interventional societies to encourage its utilization over femoral access 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…A multivariable risk model indicated that bivalirudin was a predictor of bleeding risk, whereas access site was not. 14 These results stand in contradistinction with those of the large randomized trials that have shown TRA to be more effective than TFA. 5,13 Although it is easy to dismiss them as observations now that powerful randomized data are available, that view would be mistaken.…”
Section: See Article By Hamon Et Almentioning
confidence: 85%
“…In the current issue of Circulation: Cardiovascular Interventions, Hamon et al 14 provide an intriguing and refreshing, if different, perspective. Their observations are taken from the EUROMAX (European Ambulance Acute Coronary Syndrome Angiography) trial of bivalirudin versus heparin begun before primary PCI in patients with ST-segmentelevation myocardial infarction, performed between 2010 and 2013.…”
Section: See Article By Hamon Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Radial access significantly reduced net clinical events by way of lower all‐cause mortality and major bleeding . Additionally, other contemporary trials have reported on the impact of access sites in patients undergoing primary PCI . The aim of the present study was to compare bivalirudin with UFH in patients with stable CAD undergoing PCI on dual anti‐platelet therapy (DAPT).…”
Section: Introductionmentioning
confidence: 99%